Sistemas híbridos de filtração e sua aplicação na indústria sucroenergética - Souza, Letícia Vitareli (Universidade Federal de São Carlos, 2020)
The increasing consumption of human beings and the expansion of urban centers are largely responsible for the increase in air pollution. This pollution tends to harm the quality of life of living beings, being harmful to their health. Thus, studying methodologies to reduce air pollution is of great value to the health of society. One of the major causes of air pollution is the industrial process, which has received stricter regulation and oversight by the government in recent decades. In the sugar-alcohol industry, biomass burning is a major source of gases and aerosols containing ions and organic compounds. This increase in the release of smoke and soot is associated with the presence of components harmful to human health, such as carcinogenic and mutagenic components. Currently, different equipment is known to remove polluting particles from the industrial disposal current in the atmosphere. These equipments include cyclones, electrostatic precipitators, filters and gas washers. Each equipment has its operating condition and efficiency, and may depend on the medium in which it is inserted with its respective characteristics, such as temperature, particle size, particle composition and flow. To increase the commercial competitiveness of the equipment, it seeks to evolve the durability, energy consumption and efficiency of the same. In this context, there are the hybrid filters, which are the junction of the principle of two or more gas-solid separation equipment in order to improve the gas filtration process. Analyzing the hybrid systems composed by the union of electrostatic precipitators and bag filters, it was possible to classify three types of such solutions: electrically energized filter, hybrid electrostatic filter and hybrid electrostatic precipitator. All these constructions allow increased particle collection efficiency smaller than 2.5 μm (PM2.5) and decreased pressure drop through the bag filter. Most of the studied hybrid systems were designed for the removal of particles from combustion gases in coal-fired plants and the present study aims to expose the principles and configurations of these hybrid systems, as well as to concentrate the main points of studies already carried out and to propose the use of these systems in the sugar and alcohol industry.
Hybrid filtration systems and their application in the sucroenergetic industry
Keywords: Filtros híbridos, filtros de mangas e eletrostáticos, Poluição do ar, Eficiência de coleta de naopartículas, Hybrid filters, Bag and electrostatic filters, Air pollution, Naoparticle collection efficiency.; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA